Clinical Utility of Preoperative Bilingual Language fMRI Mapping in Patients with Brain Tumors. Issue 2 (10th February 2020) - Leung, Lok Wa Laura; Unadkat, Prashin; Bertotti, Melina More; Bi, Wenya Linda; Essayed, Walid Ibn; Bunevicius, Adomas; Chavakula, Vamsidhar; Rigolo, Laura; Fumagalli, Luca; Tie, Ziyun; Golby, Alexandra J.; Tie, Yanmei
ABSTRACT: BACKGROUND AND PURPOSE: Previous literature has demonstrated disparity in the postoperative recovery of first and second language function of bilingual neurosurgical patients. However, it is unclear to whether preoperative brain mapping of both languages is needed. In this study, we aimed to evaluate the clinical utility of language task functional MRI (fMRI) implemented in both languages in bilingual patients. METHODS: We retrospectively examined fMRI data of 13 bilingual brain tumor patients (age: 23 to 59 years) who performed antonym generation task‐based fMRIs in English and non‐English language. The usefulness of bilingual language mapping was evaluated using a structured survey administered to 5 neurosurgeons. Additionally, quantitative comparison between the brain activation maps of both languages was performed. RESULTS: Survey responses revealed differences in raters' surgical approach, including asleep versus awake surgery and extent of resection, after viewing the language fMRI maps. Additional non‐English fMRI led to changes in surgical decision‐making and bettered localization of language areas. Quantitative analysis revealed an increase in laterality index (LI) in non‐English fMRI compared to English fMRI. The Dice coefficient demonstrated fair overlap (.458 ± .160) between the activation maps. CONCLUSION: Bilingual fMRI mapping of bilingual patients allows to better appreciate functionally active language areas that may be neglected in single language mapping. Utility of bilingual mapping was supported by changes in both surgical approach and LI measurements, suggesting its benefit on preoperative language mapping.